Analisis Sustainable Development Goals (SDGs) Filantropi Cilik Di LAZISMU Pamekasan - Matnin; Abdul Bari; Shofiyatus Sholihah; Aceng Badruzzaman (DPPM Universitas Pelita Bangsa, 2024)
This study aims to determine how the application and utilization of small philanthropy and analyze the Sustainable Development Goals (SDGs) on small philanthropy at LAZISMU Pamekasan. The research method used in this research is a qualitative approach method, which is a research procedure that produces descriptive data in the form of written or spoken words from people and observable behavior. The data collection techniques used are observation, interviews and documentation. Based on the research results, the analysis of Sustainable Development Goals (SDGs) in small philanthropy at LAZISMU Pamekasan is as follows: (1) The application of small philanthropy in LAZISMU Pamekasan has two models, namely piggy banks and student donors; (2) There are three aspects in its utilization, namely the religious aspect, social aspects, and education aspect; (3) Sustainable Development Goals (SDGs) of children's philanthropy in three pillars, namely social, environmental, and economic.